Assessment of Sensitivity and Validity Hydrodynamic Model in Cisadane Using Delft3d Flow Model - Pasma, Gumilang Ramadhan; Suharyanto, Hamzah Haru Radityo; Khoirunnisa, Hanah; Wijayanti, Reni; Gumbira, Gugum; Rachman, Reno Arief (Marine Science Department Diponegoro University, 2024)
The National Capital Integrated Coastal Development (NCICD) program was prioritized as a disaster reduction technology within the annual target of BRIN in 2022. It is a part of the North Java Coastal Integrated Development Program project. A coastal reservoir development plan at the Cisadane River estuary is one of the outcomes. In this case, hydrodynamic modelling is needed to acquire hydrodynamic properties under the existing condition of Cisadane downstream, and it applied the Delft3D-FLOW model. The bathymetric data used in this simulation was obtained from the assimilation of national bathymetric data with a grid spacing of 180 m and field survey data with a horizontal resolution of 10 m and transect spacing of 200 m seaward of the Cisadane estuary. It has interpolated in a regular structured grid with 100 m and 50 m grid spacing. In addition, other data used are three hourly wind data downloaded from the European Centre for Medium-Range Weather Forecasts (ECMWF) and the daily discharge of the Cisadane River in 2021. Astronomical water level data generated from TPXO 7.2 and TPXO 8 were used in the boundary conditions. These data are simulated using the two and three-dimensional flow model Delft3D-FLOW during November 1 – 15, 2021, using four manning coefficients (n) values, which are 0.03; 0.035; 0.04; and 0.045. The validation formulation used Normalization Root Mean Square Error (NRMSE), resulting in 5.3 - 9.6% for all the manning values and domains. The highest correlation coefficient of current velocity (u-v components) is acquired in the 10 km2 domain with 0.797 for the L3 (bottom layer).